C-Terminal residue optimization and fragment merging: discovery of a potent peptide-hybrid inhibitor of Dengue protease - Behnam, Mira A. M.; Nitsche, Christoph; Vechi, Sergio; Klein, Christian D. (ACS medicinal chemistry letters, 2014)
Dengue virus protease is a promising target for the development of antiviral drugs. We describe here a two-step rational optimization that led to the discovery of the potent inhibitor 35 with nanomolar binding affinity at dengue protease serotype 2 (IC50 = 0.6 μM, Ki = 0.4 μM). First, a large number of natural and non-natural amino acids were screened at the C-terminal position of the previously reported, canonical peptide sequence (Cap-Arg-Lys-Nle-NH2). Compared to the reference compound 1 (Bz-Arg-Lys-Nle-NH2, IC50 = 13.3 μM), a 4-fold higher inhibitory potential was observed with the incorporation of a C-terminal phenylglycine (compound 9, IC50 = 3.3 μM). Second, we applied fragment merging of 9 with the previously reported thiazolidinedione peptide hybrid 33 (IC50 = 2.5 μM). This approach led to the fusion of two inhibitor-fragments with micromolar affinity into a 20-fold more potent, competitive inhibitor of dengue protease.
Gesehen am 04.09.2020